2015
DOI: 10.1002/ams2.167
|View full text |Cite
|
Sign up to set email alerts
|

Temporal intrailiac balloon occlusion for the treatment of intractable pelvic fracture hemorrhage

Abstract: Case: A 48-year-old schizophrenic man sustained multiple injuries following a fall. Unstable pelvic fractures were diagnosed in the emergency department. The patient's hemodynamic status was stabilized following bilateral internal iliac artery embolization using a gelatin sponge. However, recurrent bleeding and an expanding retroperitoneal hemorrhage occurred 1 h after transcatheter arterial embolization.Outcome: Using temporal intrailiac balloon occlusion, with preperitoneal gauze packing, the patient's hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Comparison results of preoperative preparations, intraoperative procedures, and postoperative efficacy confirmed that gauze packing Case Report Pelvic gauze packing combined with an external fixator for the treatment of unstable pelvic fractures with a huge retroperitoneal hematoma: a case report was generally better than hemostasis with intervention. Ishida et al reported that multiple methods, including transcatheter arterial embolization, preperitoneal pelvic packing, and external fixation of the pelvis, can be used to comprehensively treat active bleeding caused by pelvic fractures (6).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison results of preoperative preparations, intraoperative procedures, and postoperative efficacy confirmed that gauze packing Case Report Pelvic gauze packing combined with an external fixator for the treatment of unstable pelvic fractures with a huge retroperitoneal hematoma: a case report was generally better than hemostasis with intervention. Ishida et al reported that multiple methods, including transcatheter arterial embolization, preperitoneal pelvic packing, and external fixation of the pelvis, can be used to comprehensively treat active bleeding caused by pelvic fractures (6).…”
Section: Introductionmentioning
confidence: 99%